Job satisfaction of employees in the life insurance industry - Phua, David Soon Keng. (2008)
This exploratory study is an attempt to understand the job satisfaction of salaried employees of the life insurance industry in Singapore. The extent to which seven hypothesised factors influence job satisfaction, namely, sex, marital status, age, education level, type of company, length of service with the company and length of service in the industry, was examined. Relationships between job characteristics, organisation characteristics and overall job satisfaction were then investigated. The best predictors of overall job satisfaction were also determined.